Pedophilia and Sexual Violence Against Children: Punishment Services and Protection - Amri, Syaiful (Universitas Islam Negeri Sumatera Utara, 2024)
Sexual The increasing cases of sexual violence against children, especially pedophilia, have attracted public attention, which finally made the government declare that 2014 is the Emergency Year of Sexual Violence against Children. This article is intended to provide an overview and also thoughts on pedophilia as sexual violence against children, and is expected to be a starting point for making policies to protect children from sexual violence. This article is a literature study that places pedophilia as a serious problem that must be immediately addressed by all aspects of government, namely society, the business world, and the government itself, both central and regional governments. Steps to save children from sexual crimes range from strict and firm legal guarantees to social support from the community. The Indonesian Ministry of Social Affairs through LKSA is committed to being the vanguard in preventing violence and protecting children. Simultaneous and comprehensive cooperation is needed from parents, the surrounding community, and government officials to ensure the success of child protection.